Portrait of Consumer Behavior: Exploring Toyota Avanza in Jombang Regency: Potret Perilaku Konsumen: Mengulik Toyota Avanza di Kabupaten Jombang - Noverta Adinda Puspa Nagara; Nuri Purwanto (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate consumer behavior regarding the Toyota Avanza car in Jombang Regency using a qualitative phenomenological approach. Data were gathered from 2 respondents who owned a Toyota Avanza through purposive sampling techniques. The findings reveal that the Toyota Avanza is highly sought after due to its numerous advantages, including good car quality, fuel efficiency, a robust engine, complete features, modern design both inside and out, and affordability. Moreover, the car's availability of spare parts and comprehensive service throughout Indonesia adds value to its appeal. These insights shed light on consumer preferences and can inform marketing strategies to optimize the appeal of the Toyota Avanza in the market. Highlight: Consumer Behavior Analysis: The study investigates consumer preferences and behavior towards the Toyota Avanza car in Jombang Regency, providing valuable insights for understanding market demand. Advantages of Toyota Avanza: The research identifies key factors driving the car's popularity, such as its good quality, fuel efficiency, powerful engine, complete features, and modern design, coupled with an affordable price. Marketing Implications: The findings offer significant implications for marketing strategies, allowing companies to leverage the car's appealing features and comprehensive service availability to optimize market positioning and attract potential customers. Keyword: Toyota Avanza, Consumer Behavior, Qualitative Phenomenological Approach, Advantages, Marketing Strategies